Melorheostosis Involving the Hip Joint - Antoine Vandendriessche; Filip Vanhoenacker (Journal of the Belgian Society of Radiology)
Teaching point: Melorheostosis is a rare sclerosing bone dysplasia, characterized by sclerosis at the periosteal and/or endosteal side of the cortex, causing undulating thickening of the bony contour resembling “dripping candle wax.”